Environmental factors between normal and superagers in an argentine cohort (2020)
Normal aging usually brings age-related cognitive decline. However, there is a group of aged individuals who have exceptional memory performance: the superagers. Objective: Our aim was to identify the environmental factors that could influence exceptional memory performance in a cohort of Argentine individuals. Methods: Forty healthy volunteers >80 years of age were classified into two groups, superagers (SA, n=20) and normal agers (NA, n=20), according to the Northwestern SuperAging Program criteria. Participants were neuropsychologically tested and evaluated on environmental aspects: working status, education, bilingualism, cognitive reserve, physical activity, social networking, clinical comorbidities, and longevity of parents and siblings. Results: Both groups were highly educated (NA=16.3±3 years; SA 15.85±2.6; p=0.6), 11.8% of the sample was still working without differences between groups. There were no differences in cognitive reserve inventory (p=0.7), physical activity engagement (p=0.423), or social network index (p=0.73). As for longevity, 44% of the siblings lived longer than 80 years of age (p=0.432) and maternal longevity was linked to SA (NA=46.7%; SA=80%; p=0.045). Conclusions: This study is a pilot approximation to the superaging population in Argentina. Our results suggest that environmental factors related to successful aging do not differentiate superaging. SA may depend on variables yet to be identified, probably of a genetic/metabolic order.